Ionotropic receptors at hippocampal mossy fibers: roles in axonal excitability, synaptic transmission, and plasticity - Ruiz, Arnaud J.; Kullmann, Dimitri M. (Frontiers in Neural Circuits, 2013)
Dentate granule cells process information from the enthorinal cortex en route to the hippocampus proper. These neurons have a very negative resting membrane potential and are relatively silent in the slice preparation. They are also subject to strong feed-forward inhibition. Their unmyelinated axon or mossy fibre ramifies extensively in the hilus and projects to stratum lucidum where it makes giant en-passant boutons with CA3 pyramidal neurons. There is compelling evidence that mossy fibre boutons express presynaptic GABAA receptors, which are commonly found in granule cell dendrites. There is also suggestive evidence for the presence of other ionotropic receptors, including glycine, NMDA and kainate receptors, in mossy fibre boutons. These presynaptic receptors have been proposed to lead to mossy fibre membrane depolarisation. How this phenomenon alters the excitability of synaptic boutons, the shape of presynaptic action potentials, Ca2+ influx and neurotransmitter release has remained elusive, but high-resolution live imaging of individual varicosities and direct patch-clamp recordings have begun to shed light on these phenomena. Presynaptic GABAA and kainate receptors have also been reported to facilitate the induction of long-term potentiation at mossy fibre – CA3 synapses. Although mossy fibres are highly specialised, some of the principles emerging at this connection may apply elsewhere in the CNS.